The Authority of the Police in Issuance of Music Performance Permits as Efforts to Control Security and Order - Dian Rahayu Windyastuti; Umar Ma'ruf (Universitas Islam Sultan Agung, 2020)
Aim This study is to determine and analyze the regulatory procedures for issuing music stage permits, the authority of the National Police in issuing permits for music performances as an effort to control security and order and factors inhibiting Polri's authority in issuing permits for music performances as an effort to control security and order. This study uses an empirical juridical approach. The conclusion of this research is about the Procedure for Issuance of Music Performance Permits, namely; The applicant brings the requirements (photocopy of ID card and musical performance record, then the officer provides a Community Service Accountability Statement, Environmental Permit Statement, Location Permit Statement, after completing a Music Performance Permit issued by the Chief of Police, which is then submitted to the permit applicant. . the authority of the National Police in issuing permits for music performances as an effort to control security and order. Provide permits and supervise public crowd activities and other community activities, Fostering the community to increase community participation, public legal awareness and obedience to the laws and regulations of the community, Maintain orderliness and ensure public safety. factors inhibiting the authority of the National Police in issuing musical performances as an effort to control security and order. There is a music stage permit that has not extended or does not make a Performance Recommendation, The time for a sudden permit application should be 7 (seven) days before the activity or event takes place, When the environmental permit statement is not approved by the environment around the location of the event